Mind the Neighbors : The Impact of Productivity and Location on Firm Turnover - Hallward-Driemeier, Mary (2012)
This paper examines the impact of firm productivity and local industrial structure on firm entry and exit in Morocco between 1985 and 2001. There is strong evidence of productivity exerting a market-cleansing role. Less productive firms are found to be more likely to exit - and locations with more productive firms attract higher rates of new firm entry. The effect of productivity operates not only in an absolute sense; a firm s relative productivity or distance to the local sector frontier matters too. First, large productivity gaps are associated with higher rates of exit, while new firms are attracted to locations with small productivity gaps. Second, local competition increases the probability of exit, although it does not encourage entry. Third, there is evidence of scale or agglomeration effects that increase firm turnover. Fourth, measures of sector diversity are not associated with lower turnover. Fifth, the geographic level at which agglomeration and competition effects are defined matters differently for exit than entry. For exit, the provincial measures are strong, while those for communes are weaker. For entry, it is the local productivity at the commune level that is more significant. This implies that competitive pressures are less geographically constrained while the potential benefits of agglomeration and spill-overs are indeed more local.